Comparison of heavy ion transport simulations: Ag + Ag collisions at Elab = 1.58A GeV. (1st May 2022) - Reichert, Tom; Elz, Alexander; Song, Taesoo; Coci, Gabriele; Winn, Michael; Bratkovskaya, Elena; Aichelin, Jörg; Steinheimer, Jan; Bleicher, Marcus
Abstract: We compare the microscopic transport models UrQMD, PHSD, PHQMD, and SMASH to make predictions for the upcoming Ag + Ag data at E lab = 1.58 A GeV ( s NN = 2.55 GeV) by the HADES collaboration. We study multiplicities, spectra and effective source temperatures of protons, π ±, 0, K ±, the η, Λ + Σ 0 and the Ξ − within these models. Despite variations in the detailed implementation of the dynamics in the different models, the employed transport approaches all show consistent multiplicities of the bulk of investigated hadrons. The main differences are in the Ξ − production, which is treated differently between UrQMD/SMASH on one side employing high mass resonance states with explicit decays to Resonance → Ξ + K + K in contrast to PHSD/PHQMD which account only non-resonant Ξ production channels. A comparison of the spectra, summarized by effective source temperatures, shows that all models provide similar source temperatures around T source = 80–95 MeV, and show substantial radial flow on the order of ⟨ v T ⟩ = 0.18 c − 0.24 c even for such a small system.